The limits of Murra's economic model - Garaycochea Mejía, Carlos F. (2010)
As part of his extensive work John Murra in 1972 proposed a model to explain the organization and functioning of the Andean economy, based on a vertical control of ecological zones. This model became the most accepted hypothesis in the field. In his article Garaycochea Mejía makes a critical analysis of this model from both a historical and an economic perspective. He examines the theoretical framework, reconstructing the model and how it functioned. He also analyzes Murra’s theoretical approaches, geographical diversity and the contribution of the economic resources of Tawantinsuyo, the application of an economic rationale, and the historicity of the model. The principal conclusion is that Murra’s model is not generally applicable to the Andean situation and that it is limited to the cases presented in 1972.